Tantangan Pengaturan Anti-treaty Shopping di Indonesia Setelah Berlakunya Multilateral Instrument - Agung Kurniawan; Ning Rahayu (Politeknik Ganesha Medan, 2022)
This paper reviews the rapidly growing empirical literature on anti-treaty shopping arrangements after the adoption of multilateral instruments, especially those relating to the application of the Principal Purpose Test (PPT). The absence of a Principal Purpose Test definition in the agreement, or an international understanding of how the PPT should be interpreted means that various parties may act differently and provide different interpretations of a transaction or arrangement. In addition, the inequalities of evidence between the tax authorities and taxpayers on the justification of transaction motives or arrangements solely for the benefit of the agreement raises the potential for tax disputes that are getting bigger because of the different perspectives built by the tax authorities and taxpayers. The purpose of this study is to examine the theoretical and empirical aspects of the challenges and obstacles in implementing the PPT arrangement in Indonesia, as well as to see the development of the arrangement from a global perspective. The research approach used in this study is to use qualitative methods with data collection techniques through documentation and literature review or literature study by providing an understanding of a social phenomenon related to the implications of implementing the Principal Purpose Test. The results and conclusions of this study lead to the urgency that the Tax Authority increasingly needs to issue regulations related to the implementation of the Principal Purpose Test in order to create legal certainty for taxpayers.